TOURISM MARKETING MIX FOR INCREASING TOURIST VISIT IN DENAI LAMA TOURISM VILLAGE - Ria Natalia Tamba; Marciella Elyanta; Sumihar Sebastiana (Jurnal Sosial Humaniora dan Pendidikan, 2022)
The purposes of this study include: to analyze the marketing mix in Denai Lama Tourism Village based on tourist characteristics to increase tourist visits in Denai Lama Tourism Village. This study uses a quantitative-qualitative approach or mix method. The data used in this study are primary data and secondary data. This study used the method of observation, interviews and questionnaires. Questionnaires were used to determine and analyze the characteristics of tourists and the marketing mix in the Tourism Village of Denai Lama. The number of samples was determined using Slovin's theory, and 100 samples were obtained. The results of the questionnaire were processed using Microsoft Excel calculations with the presentation of the data using a pie chart. The results of this study indicate that the characteristics of tourists in Denai Lama Tourism Village are dominated by age: 21-30 years old, educational background: high school, income Rp. 1,100,000- Rp. 2.000.000, Gender: Women with family cycle: Married Children aged 2-12 years. Based on the psychographic aspect of the mid-centric tourist type. The application of the marketing mix in the Denai Lama Tourism Village has been implemented well, but there are still certain things that must be considered and improved so that tourists increase. Of the 7Ps of the marketing mix in the Denai Lama Tourism Village, the elements of Place, Physical Evidence and Promotion have the lowest value among other elements, so the marketing mix elements really need to be considered and improved to increase tourist visits in the Denai Lama Tourism Village.